An integrated TTCN–3 test framework architecture for interconnected object–based internet applications. (2nd December 2013) - Stepien, Bernard; Peyton, Liam; Shang, Ming; Vassiliou–Gioles, Theofanis
The internet is being transformed by rich interconnected object–based applications that support session–based interactions between users and applications over a variety of protocols (HTTP/s, SOAP, SIP). In this paper, we analyse and demonstrate the key benefits and advantages of TTCN–3, especially in terms of costs, as a test language and framework for testing internet applications. The integration of TTCN–3 and object–based unit test frameworks can provide superior testing of interconnected object–based internet applications but is currently limited by a small flaw in the TTCN–3 concrete layer architecture. We propose a refinement to the TTCN–3 standard which enables seamless integration with object–based unit test–frameworks. An existing TTCN–3 vendor has already incorporated the changes in the latest version of their tool and ETSI has established a committee to modify the TTCN–3 standard accordingly. We demonstrate the benefits with a series of examples involving both SIP and HTTP–based internet applications.